Inclusive Higher Education in United Arab Emirates: Will Perceived Knowledge of Inclusion Impact Positively on University Students’ Attitudes Towards Learning With Peers With Disabilities? - Alzyoudi, Mohammed; Opoku, Maxwell Peprah; Moustafa, Ashraf (Frontiers in Education, 2021)
Inclusive education is widely acknowledged as useful in promoting the involvement of all students. One core objective for the implementation of inclusive education is to promote acceptance and peaceful co-existence between students with disabilities and typically developing peers in classrooms. Since 2006, the federal government of the United Arab Emirates (UAE) has developed policies aimed at achieving inclusive education at all academic levels. However, the link between typically developing students’ perceived knowledge of inclusive education and their attitudes towards their peers with disabilities is understudied in the UAE context, especially at the university level; hence, this study aspired to assess those views. A revised Chedoke-McMaster Attitudes towards Children with Handicaps (CATCH) scale was adapted and completed by 233 university students. The data were subjected to a t-test, an analysis of variance (ANOVA), and linear regression. The findings showed feelings of negativity towards peers with disabilities. Interestingly, those who indicated they were unaware of inclusive policies held more positive perceptions of their peers with disabilities than those who stated otherwise. The study’s limitations, recommendations for future research, and implications for policymaking and practices are also discussed.